Phytohormones unlocking their potential role in tolerance of vegetable crops under drought and salinity stresses - Chen, Jun; Pang, Xin (Frontiers in Plant Science, 2023)
Globally, abiotic stresses are drastically reducing the productivity of vegetable crops. Among abiotic stresses, drought and salinity are more challenging constraints for the sustainable production of vegetables. A great variety of vegetables are facing dry and hot summer spells, poor water availability, and higher salinity mainly due to irrigation with brackish water. Vegetables are considered higher water-dependent crops, requiring water for proper growth and yield. Drought and salinity impair plant metabolism. The disruption in plant metabolism leads to a reduction in growth, developmental processes, and ultimately crop yield. Appropriate management measures are needed to cope with the adverse effects of drought and salinity. Different agronomic and molecular approaches contributed to improving tolerance. Therefore, the present review significantly explores the impact of phytohormones on vegetable crops under drought and salinity stresses. Phytohormones (salicylic acid, melatonin, jasmonates, Brassinosteroids, ascorbic acid, and numerous others) can be sprayed for improvement of plant growth, yield, and photosynthetic pigments by modulation of physiological and biochemical processes. In this manner, these phytohormones should be explored for sustainable production of vegetable crops growing under abiotic stress conditions.